Analisis Kinerja Traksi Kendaraan Roda Tiga Dengan Transmisi Otomatis - Pradnyana, I Kd Arik Dwi; Atmika, I Ketut Adi; Budiana Panindra, I Made Dwi (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstract Traction control system is one of the technology that are currently developing in automotive technology. It is maintaining the stability of a vehicle. Recent years, there have been many commercial vehicles based on motorcycles. These commercial vehicles in the form of three-wheeled motorcycles usually use for trading or transporting garbage.The purpose of this study was to determine the traction characteristics of three-wheeled vehicles with automatic transmission systems in overcoming various kinds of obstacles. This test was carried out using a dyno test tool to obtain vehicle torque. Furthermore, research of the data collected is carried out to analyse the characteristics of traction, incline resistance, obstacles in the contact area of the tire and the road. Traction characteristic and transmission vehicle performance tested by using VIAR Karya Bit 100. From the result of this study, it can be found that the traction curve vs speed showed that there were a lot of wasted traction. This condition due to loss on CVT (continuously variable transmission) system, so that the traction was not reached the ideal conditions. For the ability of climbing from VIAR Karya Bit 100 without load, it could pass road slope maximum 27.40, then if it was with 100 kg of load, it could pass slope road maximum 19.09 and if it was with 150 kg, it could pass the slope road as 16.39. On previous study of transmission manual, it showed that Fmax between tires area and road in unloaded condition experiencing slip at the first level of transmission and the second transmission on wet asphalt, wet concrete, dry asphalt, and dry concrete. Meanwhile with 100 kg loading conditions experiencing slip on the first level of transmission on wet asphalt. And for 150 kg loading conditions, it could pass all all road obstacles without slipping. Keywords : standar transmission, traction, torque, power, tricycle.